Constitution and constitutionalism - Moten, Abdul Rashid (Cengage Learning Asia Pte Ltd., 2008)
A constitution is a body of formal and effective rules and regulations that govern the relationship between people and formal institutions of a state. It is a body of fundamental rules which determines the organisation or structure of the government, and determines the relations among the organs of the government. It also contains a statement of the rights and duties of the citizens of the country. In democratic systems, the constitution is considered a fundamental social contract among citizens, where government receives its powers from the people and is bound by an express set of human rights. The constitution is thus considered a statute superior to "ordinary" statutes, which it can overrule, and is usually protected by special courts. This chapter analyses the nature and features of the Constitution of Malaysia and examines the way the Constitution produces a government limited by law.